PENGARUH SISTEM INFORMASI AKUNTANSI DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN HOTEL TRANSIT SYARIAH MEDAN - ADIKO, RIDHO GILANG; Saniah, Nurul (JURNAL AKUNTANSI DAN INVESTASI, 2020)
This research was conducted to see the effect of accounting information systems and work motivation on employee performance at the hotel transit syariah Medan.. The population in this study amounted to 32 people consisting of all employees of the hotel transit syariah Medan.The data collection technique in this study was conducted using a questionnaire distributed to respondents. The analysis technique used in this research is multiple linear regression analysis techniques.The results of the analysis obtained from this study, it is known that the results of the t test for variable X1 show that the accounting information system has no effect on employee performance, and for X2 it is found that work motivation has an effect on employee performance. For the F test, the results show that the accounting information system variables and work motivation simultaneously affect the performance of the employees of the hotel transit syariah Medan. The amount of the Adjusted R Square coefficient of determination obtained is 81.9%..